Performance Investigations of a Quad-band Microstrip Antenna for Body Wearable Wireless Devices - Karthik, Varshini; Rao, T. Rama (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This research work proposes a microstripbased quad-band monopole antenna for body Wearable Wireless Devices (WWD) for Wireless Body Area Network (WBAN) applications. Ultra high frequency (UHF) and Ultra wide band (UWB) technology have been known for their efficiency to meet power, size and distance considerations for WBANs. The designed antenna resonates at four frequencies, 1.8, 2.4, 5.0 and 8.9 GHz covering licensed and license-free wireless technologies. The antenna design considers the electromagnetic (EM) effects due to the interaction of body tissues with the radio frequency (RF) waves, which are very different when compared to their interaction with free space. The performance of the antenna is investigated in terms of radiation efficiency, total gain, specific absorption rate (SAR), and thermal effects (short and long term). A simplified, human body tissue layer model is used for simulations utilizing EM computations. Simulated and experimental results are paralleled and are found to be in good agreement.